Peningkatan Kecerdasan Spiritual Siswa Melalui Kegiatan Keagamaan di SMA N 1 Wonosobo - Aina Sifa Mustika Putri; Sri Haryanto; Vava Imam Agus Faisal (Journal of Student Research, 2024)
This thesis aims to: 1) Determine the condition of students' spiritual intelligence at SMA N 1 Wonosobo 2) Determine the application of religious activities to increase spiritual intelligence at SMA N 1 Wonosobo 3) Determine the supporting and inhibiting factors for increasing students' spiritual intelligence through religious activities at SMA N 1 Wonosobo. This research uses a qualitative descriptive approach to collect information and describe and interpret data. Data was obtained through observation, in-depth interviews with school principals, teachers supervising religious activities, and analysis of related documents.The research results show that students' active participation in religious activities contributes positively to increasing the dimensions of spiritual intelligence, including self-awareness, awareness of spiritual values, as well as the ability to be empathetic and meaningful in living daily life. These findings indicate that the integration of religious activities in the school environment can be an effective strategy in fostering students' spiritual intelligence, which in turn plays a role in their character development and emotional well-being.